Back Cover Image. Issue 9 (5th September 2021) - Shan, Lutong; Wang, Yiren; Liang, Shuquan; Tang, Boya; Yang, Yongqiang; Wang, Ziqing; Lu, Bingan; Zhou, Jiang
Abstract : Authors reported the biphasic vanadate, i.e., Na1.2 V3 O8 /K2 V6 O16 ·1.5H2 O (designated as Na0.5 K0.5 VO), and detected the interfacial Adsorption‐Insertion mechanism induced by phase boundaries (DOI: 10.1002/inf2.12223 ). First‐principles calculations indicated that large amount of Zn 2+ and H + ions would be absorbed by the phase boundaries and most of them would insert into the host structure, which not only promote the specific capacity, but also effectively reduce diffusion energy barrier towards faster reaction kinetics. As a result, the aqueous Zn/Na0.5 K0.5 VO performs excellent rate capability as well as long‐term cycling performance, for example, a stable capacity of 267 mA h g ‐1 after 800 cycles at 5 A g ‐1 can be achieved. Abstract : Authors reported the biphasic vanadate, i.e., Na1.2 V3 O8 /K2 V6 O16 ·1.5H2 O (designated as Na0.5 K0.5 VO), and detected the interfacial Adsorption‐Insertion mechanism induced by phase boundaries (DOI: 10.1002/inf2.12223 ). First‐principles calculations indicated that large amount of Zn 2+ and H + ions would be absorbed by the phase boundaries and most of them would insert into the host structure, which not only promote the specific capacity, but also effectively reduce diffusion energy barrier towards faster reaction kinetics. As a result, the aqueous Zn/Na0.5 K0.5 VO performs excellent rate capability as well as long‐term cycling performance, for example, a stable capacity of 267 mA h g ‐1 after 800 cycles at 5 A g ‐1 can be achieved.